Proceso de atención de enfermería en lactante menor con gastroenteritis más infección a las vías urinarias. - Cabrera Barragán, Joel Everardo (2024)
Gastroenteritis is defined as an irritation of the lining of the gastrointestinal tract, which commonly manifests itself with symptoms such as fever, nausea, vomiting, diarrhea, and especially pain in the abdomen. Diarrhea is distinguished by an increase in the volume or quantity of stool, or a reduction in firmness of stool relative to previous evacuations. It is classified as acute if it persists for less than 3-4 weeks and persistent or chronic if it lasts longer. This clinical case presents the medical history of a female infant of approximately 11 months, who arrives at a health center with symptoms that include liquid stools approximately ten times in four hours, according to the mother. Additionally, the patient presents vomiting, fever, and mouth ulcers. She is hospitalized along with her mother, receiving initial treatment of intravenous rehydration and medication prescribed by a doctor. Patient progress is monitored through laboratory analysis and the Nursing Care Process is applied. The diagnostic approach for the present case study involves history analysis, physical evaluation, and clinical determination of the patient.